Exopolysaccharide production by Ganoderma lucidum immobilised on polyurethane foam in a repeated-batch fermentation - Wan-Mohtar, W. A. A. Q. I. (Elsevier Ltd, 2016)
Exopolysaccharide (EPS) production by Ganoderma lucidum BCCM 31549 immobilised on polyurethane foam (PUF) cubes exhibited high ability for continuous EPS production in a repeated-batch fermentation (RBF). RBF by immobilised mycelium was optimised for broth replacement time point and broth replacement ratio. Interestingly, seven batches could be fermented consecutively in the shake flask for 55 days using 80% broth ratio and at day 13 time point, where this smart immobilised approach was deployed. Fermentation time was reduced from 13 days to 6 days, and the medium usage was also reduced due to the broth replacement volume procedure. Critically, immobilised G. lucidum mycelium grown on PUF cubes could be reused at least for seven successive cycles without any loss of EPS efficiencies with the PUF cubes retained the original structure, pointing out to be an ideal immobilisation matrix. The EPS productivity in immobilised culture at 0.045 g/L day−1 was higher than the value in a freely suspended culture (0.029 g/L day−1). The proposed immobilisation strategy proved that PUF as a physical carrier would provide an economical solution to enhance EPS production for extended liquid fermentation of mushrooms.